Effects of Aluminium Toxicity on Root and Shoot Growth Of Rice and Chickpea Seedlings - Samad, Rifat; Rashid, Parveen; Karmoker, JL (Bangladesh Journal of Botany, 2021)
Increasing concentrations of aluminium progressively declined primary root length and number of lateral roots in rice and chickpea seedlings grown in rhizobox. It also inhibited the root and shoot length, dry weight of root and shoot of rice and chickpea seedlings grown in solution culture. On the other hand, it enhanced shoot/root length ratio and dry weight ratio for both the genera. Bangladesh J. Bot. 50(4): 1195-1201, 2021 (December)